INVESTIGATING THE EFL TEACHERS’ ATTITUDES TOWARD THE INTEGRATION OF WEB 2.0 TOOLS IN TEACHING ENGLISH AT ISLAMIC BOARDING SCHOOLS - supiani supiani (Universitas Wiralodra, 2019)
The purposes of this study are to investigate EFL teachers’ attitudes toward the integration of Web 2.0 tools in teaching English at Islamic Boarding Schools and to examine the extent of using Web 2.0 tools in teaching English at Islamic Boarding Schools. There were 18 EFL teachers from Islamic Boarding Schools in South Kalimantan province, Indonesia participated in this study. The data were taken from the EFL teachers were gathered by using the questionnaire, analyzed using descriptive statistics and followed up in the interview. The results of the study indicated that most EFL teachers have positive attitudes toward the integration of Web 2.0 tools in teaching English and percentages of their attitudes were high, with 75%. The findings also showed that almost all of the EFL teachers strongly agreed that Web 2.0 tools made them more efficient and interesting in the teaching and learning process at the class. The majority of EFL teachers that integrated towards Web 2.0 tools in teaching English used tools such as YouTube, Google Sites, blogs, and wikis. However, there were the barriers that were faced by the EFL namely lack of technological equipment in school, limited time at the class to explore the technology and the students were not allowed to bring communication tools at the class, so Web 2.0 tools have not been fully explored at the English class. Keywords: EFL teachers attitudes, The integration of Web 2.0 tools, Teaching English